Synthetic environment for forward scattering radar software development: article - Ab Gapor, Siti Mas Hidayu (2015)
There are a lot of measurement and analysis has been done by previous FSR researcher. The data collected from their experimental is very important to other FSR researcher. The needed of the program or software application such as Graphical User Interface (GUI) that can gather all the database of the experimental result for solving their routine problems such as repetition work done. This paper describes the Synthetic Environment for Forward Scattering Radar Software Development. The Design for Software Development is described. The system can estimate the performance and able to predict the signal strength under variety of environmental conditions and kind of targets.